Identification of gene signatures associated with ulcerative colitis and the association with immune infiltrates in colon cancer - Pan, Zhaoji; Lin, Hao; Fu, Yanyan; Zeng, Fanpeng; Gu, Feng; Niu, Guoping; Fang, Jian; Gu, Bing (Frontiers in Immunology, 2023)
Inflammatory bowel diseases (IBD) are common inflammatory disorders of the gastrointestinal tract that include ulcerative colitis (UC) and crohn's disease (CD). Intestinal immune dysfunction has been identified as one of the important factors in the pathogenesis of UC. However, the underlying mechanisms that currently regulate dysfunctional immune cell and inflammatory phenotypes remain to be fully elucidated. We performed differential gene analyses using microarray datasets GSE24287, GSE87466, GSE102133 and GSE107499, which included 376 samples. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) were used to analyze the common differentially expressed genes (DEGs) in these datasets and explore the underlying biological mechanisms. CIBERSORT was used to evaluate immune cell infiltration in UC. Cytoscape was performed to screen hub genes. Gene Set Enrichment Analysis (GSEA) was utilized to explore potential biological mechanisms of hub genes. Then, hub genes were analyzed by microarray datasets GSE92415, GSE53306, GSE59071, Tumor Immune Estimation Resource (TIMER), and tissues of patients with associated UC and DSS-induced colitis in mice. Based on the results of Cytoscape analyses, we identified three core genes which are CCL3, MMP3 and TIMP1. We further verified these genes were positively associated with active UC and served as a biomarker for active UC.  Moreover, the expression of CCL3, MMP3 and TIMP1 in the associated intestinal mucosa was decreased in patients with active UC who responded to Golimumab therapy. In addition, there were significant positive correlation between CCL3, MMP3 and TIMP1 expression and different types of immune cells, including CD8+ T cells, macrophages, neutrophils, and dendritic cells in the colon adenocarcinoma (COAD). Moreover, CCL3, MMP3 and TIMP1 expression were strongly correlated with different sets of immune markers. CCL3, MMP3 and TIMP1 are hub genes in the progression of UC and may serve as a novel pharmacological regulator of UC, providing a new target for the treatment of UC, and may serve as biomarkers for immune infiltration in colon cancer.